2017
DOI: 10.1016/j.carbon.2017.05.068
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling of graphene from Ni(111) via formation of an interfacial NiO layer

Abstract: The combination of the surface science techniques (STM, XPS, ARPES) and density-functional theory calculations was used to study the decoupling of graphene from Ni(111) by oxygen intercalation. The formation of the antiferromagnetic (AFM) NiO layer at the interface between graphene and ferromagnetic (FM) Ni is found, where graphene protects the underlying AFM/FM sandwich system. It is found that graphene is fully decoupled in this system and strongly p-doped via charge transfer with a position of the Dirac poi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 56 publications
11
48
0
Order By: Relevance
“…4: (c) and inset of (i)) confirming the effective decoupling of graphene from the underlying NiO layer. The decoupling of graphene from NiO is also supported by the present XPS data as well as by the recent ARPES and density-functional theory (DFT) studies [30] where p-doping of graphene was observed.…”
Section: Oxygen Intercalation In Gr/n Ml-ni/ir(111): Stm Morphologysupporting
confidence: 85%
“…4: (c) and inset of (i)) confirming the effective decoupling of graphene from the underlying NiO layer. The decoupling of graphene from NiO is also supported by the present XPS data as well as by the recent ARPES and density-functional theory (DFT) studies [30] where p-doping of graphene was observed.…”
Section: Oxygen Intercalation In Gr/n Ml-ni/ir(111): Stm Morphologysupporting
confidence: 85%
“…[53,54] Experimental Section The bondedo xygen mostly desorbs at approximately 580 K, with partial reaction to boron oxides.…”
Section: Discussionmentioning
confidence: 99%
“…Only increased temperatures and orders of magnitude highero xygen pressure have resulted in intercalation. [53,54] Experimental Section…”
Section: Discussionmentioning
confidence: 99%
“…However, the high crystalline quality of the prepared samples is accompanied by perturbations in the electronic structure of single layer graphene due to the presence of the substrate, leading to the complete loss of the massless character of carriers around the Fermi energy ( E F ) in some cases. For strongly interacting systems, such as graphene on Ni(111), Rh(111), Ru(0001), an efficient decoupling can be performed by the intercalation of oxygen or other elements, leading to the restoration of the linear energy–momentum dispersion near E F . Even for the substrates considered to show only weak interaction with graphene, such as Ir(111), decoupling schemes based on intercalation are also used to further reduce the influence of the substrate and to produce a nearly free‐standing graphene .…”
Section: Introductionmentioning
confidence: 99%